Direct nephrotoxicity of Russell's viper venom demonstrated in the isolated perfused rat kidney. - Ratcliffe, P; Pukrittayakamee, S; Ledingham, J; Warrell, D (1989)
Envenoming by Russell's Viper (Vipera russelli) is an important cause of acute renal failure. The mechanism of renal damage is unresolved. It is difficult to obtain evidence of a direct nephrotoxic action because of the coincidental disturbance to the systemic circulation. We studied the action of Russell's Viper venom on the function of the isolated perfused rat kidney. Direct nephrotoxic action was indicated by a dose dependent decrease in inulin clearance and an increase in fractional excretion of sodium seen at venom concentrations down to 50 ng/ml, a concentration likely to be achieved in the human circulation after envenoming. The isolated perfused kidney was also used to assess the efficiency of antivenom and for a comparison with snake venoms from the Thai cobra (Naja kauothia) and the Nigerian Saw-Scaled Viper (Echis ocellatus).